Angiogenesis in the human thymoma assessed by subclassification of tumor-associated blood vessels and endothelial cells proliferation - Raica, M; Mogoantă, L; Kondylis, A; Cîmpean, Anca Maria (Romanian journal of morphology and embryology, 2010)
The prognostic value of tumor-associated angiogenesis is still a subject of debate. As microvascular density and the expression of different growth factors were not demonstrated to be good predictors of the response to antiangiogenic and antivascular therapy, there is a strong need to search for more sensitive markers. In the present study we evaluated by double immunohistochemical staining the profile of tumor-associated blood vessels and the rate of endothelial cell proliferation in patients with thymoma (n=38). Results were compared with specimens of normal thymus and from patients with myasthenia gravis. We found a significant increase in the number of immature and intermediate blood vessels in the tumor area of thymoma, regardless the histological type of the tumor. Proliferating endothelial cells were found in 15 cases, and co-expression of Ki67 and CD34 had the highest value in immature vessels. Both blood vessel type and endothelial cell proliferation significantly correlated with invasive thymoma. Based on these findings, it can be assumed that the type of tumor-associated vessel together with endothelial cell proliferation are useful predictors of invasion, immature and intermediate vessels can be targeted with antivascular drugs and endothelial cell proliferation could be used as a good predictor of the response to antiangiogenic therapy.